Sequential statistical hypotheses testing for discrete random data with block structure - Kharin, Alexey Yu. (Journal of the Belarusian State University. Mathematics and Informatics, 2026)
An important mathematical problem of computer data analysis – the problem of sequential statistical testing of simple hypotheses on probability distributions of discrete random data with a block structure – is considered. Explicit expressions of the sequential tests statistics, transparent for interpretation and convenient for computer realisation, are derived. An approach to calculate the performance characteristics – error probabilities of the decisions and mathematical expectations of the random number of observations required to guarantee the requested accuracy for decision rules – is developed. Asymptotic expansions for the mentioned performance characteristics under distortion of the hypothetical probability model are constructed.